1978
DOI: 10.1136/hrt.40.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Regional myocardial blood flow in patients with chest pain syndromes and normal coronary arteriograms.

Abstract: To evaluate possible disorders of regional myocardial blood flow in patients with chest pain syndromes and normal coronary arteriograms, we studied 21 patients with intracoronary injections of Xenon-133. Thirteen patients were restudied during an intervention: 6 patients received glyceryl trinitrate and 7 patients had contrast agent-induced hyperaemia. Patients were divided into 3 clinical groups: 7 patients had classic angina, 7 patients had a mixture of typical and atypical chest pain, and 7 patients had ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Recently coronary vasodilator reserve (CVR) in syndrome X has been the object of many studies. [2][3][4][5][6][7][8][9] Positron emission tomography (PET), in particular, has permitted the noninvasive quantifica-tion of regional MBF and CVR.79 However, in none of these studies were syndrome X patients compared directly with matched normal control subjects. Generally, the control groups have consisted of patients with "atypical" chest pain or patients with chest pain but no changes on the stress ECG.…”
mentioning
confidence: 99%
“…Recently coronary vasodilator reserve (CVR) in syndrome X has been the object of many studies. [2][3][4][5][6][7][8][9] Positron emission tomography (PET), in particular, has permitted the noninvasive quantifica-tion of regional MBF and CVR.79 However, in none of these studies were syndrome X patients compared directly with matched normal control subjects. Generally, the control groups have consisted of patients with "atypical" chest pain or patients with chest pain but no changes on the stress ECG.…”
mentioning
confidence: 99%
“…14 " 16 The abnormal thallium-201 perfusion study results may have been related to undetected coronary artery disease in hypertensive patients, increased oxygen demand caused by increased left ventricular mass, 17 inadequate coronary reserve, 18 ' 19 altered hemodynamics, 20 ' 21 or to a combination of these or other, as yet unrecognized, factors. 22 " 24 The increased incidence of abnormal stress test results in hypertensive patients in the absence of angiographic coronary artery disease noted in earlier radionuclide ventriculographic studies 4 and the trends observed in the present study of thallium perfusion may reflect supply-demand imbalance independent of coronary anatomy.…”
Section: Discussionmentioning
confidence: 99%